Metabolite Profile Changes in Xylem Sap and Leaf Extracts of Strategy I Plants in Response to Iron Deficiency and Resupply - Rellán-Álvarez, Rubén; El-Jendoubi, Hamdi; Wohlgemuth, Gert; Abadía, Anunciación; Fiehn, Oliver; Abadía, Javier; Álvarez-Fernández, Ana (Frontiers in Plant Science, 2011)
The metabolite profile changes induced by Fe-deficiency in leaves and xylem sap of several Strategy I plant species have been characterized. We have confirmed that Fe deficiency causes consistent changes both in the xylem sap and leaf metabolite profiles. The main changes in the xylem sap metabolite profile in response to Fe deficiency include consistent decreases in aminoacids, N-related metabolites and carbohydrates and increases in TCA cycle metabolites. In tomato, Fe-resupply causes a transitory flush of xylem sap carboxylates, but within one day the metabolite profile of the xylem sap from Fe-deficient plants becomes similar to that of Fe-sufficient controls. The main changes in the metabolite profile of leaf extracts in response to Fe deficiency include consistent increases in aminoacids and N-related metabolites, carbohydrates and TCA cycle metabolites. In leaves, selected pairs of aminoacids and TCA cycle metabolites show high correlations, with the sign depending of the Fe status. These data suggest that in low photosynthesis, C-starved Fe-deficient plants anaplerotic reactions involving aminoacids can be crucial for survival in the short-term.